Pemberdayaan Kreativitas Anak Melalui Kegiatan Pendidikan Agama Dan Permainan Pendidikan Jasmani Di Gampong Lambheu Kecamatan Darul Imarah Kabupaten Aceh Besar - Syahrianursaifi Syahrianursaifi; Musran Musran; Rawi Juwanda; Asyifa Faradila (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2026)
This community service program aims to enhance children's creativity through the integration of religious education and physical education games in Gampong Lambheu, Darul Imarah District, Aceh Besar Regency. The method employed a participatory and educational approach consisting of needs assessment, planning, implementation, and evaluation stages. The participants included 50 elementary school children and mosque youth. Data were collected through observation, questionnaires, and simple pre-test and post-test instruments.The results of the program showed improvements across all indicators: children's participation increased from 60% to 90%, creativity from 50% to 75%, religious competence from an average score of 65 to 80, and social cooperation skills from 55% to 85%. In addition, positive responses reached 92% from participants and 88% from parents.These findings indicate that the integrative learning model based on religious education and physical education games is effective in enhancing children's overall development, including spiritual, cognitive, social, and physical aspects. This program also has the potential to be replicated as a community-based child empowerment model.